Strategic Planning Impact on Banks Employees’ Performance: Palestine - Sameh Rasheed Abu Khader, Sharif Musbah Abu Karsh (International Journal of Advanced Science and Technology, 2020)
This study aims to evaluate the impact of strategic planning on employees’ performance in the banks operating in Palestine, and to assess the appropriateness of the strategic plans with the bank’s vision and mission, also assess the appropriateness of resources with plans.